Panobinostat in combination with bortezomib in patients with relapsed or refractory peripheral T-cell lymphoma: an open-label, multicentre phase 2 trial. Issue 8 (August 2015) - Tan, Daryl; Phipps, Colin; Hwang, William Y K; Tan, Soo Yong; Yeap, Chun Hsien; Chan, Yiong Huak; Tay, Kevin; Lim, Soon Thye; Lee, Yuh Shan; Kumar, Sathish Gopalakrishnan; Ng, Soo Chin; Fadilah, S; et al.
Summary: Background: Patients with relapsed or refractory peripheral T-cell lymphoma have a poor prognosis after conventional chemotherapy. Approved novel agents have only modest single-agent activity in most subtypes of peripheral T-cell lymphoma. Panobinostat is a potent oral pan-deacetylase inhibitor. Findings of many preclinical studies have shown synergistic antilymphoma activity when panobinostat is combined with the proteasome inhibitor bortezomib. We aimed to study the effect of panobinostat and bortezomib in patients with relapsed or refractory peripheral T-cell lymphoma. Methods: In this open-label, multicentre phase 2 trial, we recruited patients aged 21 years or older with relapsed or refractory peripheral T-cell lymphoma who had received at least one previous line of systemic therapy from five tertiary hospitals in Singapore, Malaysia, and South Korea. Patients received 20 mg oral panobinostat three times a week and 1·3 mg/m 2 intravenous bortezomib two times a week, both for 2 of 3 weeks for up to eight cycles. The primary endpoint was the proportion of patients who achieved an objective response in accordance with the International Working Group revised response criteria; analyses were by intention to treat. The study is completed and is registered withClinicalTrials.gov, numberNCT00901147 . Findings: Between Nov 9, 2009, and Nov 26, 2013, we enrolled 25 patients with various histological subtypes of peripheral T-cell lymphoma. Of 23 patients assessable for responses, ten (43%, 95% CI 23–63) patients had an objective response, of which five were complete responses. Serious adverse events were reported in ten (40%) of 25 patients. Common treatment-related grade 3–4 adverse events included thrombocytopenia (17 [68%]), neutropenia (ten [40%]), diarrhoea (five [20%]), and asthenia or fatigue (two [8%]). We recorded peripheral neuropathy of any grade in ten (40%) patients. Interpretation: Combined proteasome and histone deacetylase inhibition is safe and feasible and shows encouraging activity for patients with peripheral T-cell lymphoma. Our findings validate those of preclinical studies showing synergism in the combination and represent a rational way forward in harnessing the full potential of novel agents in peripheral T-cell lymphoma. Funding: Novartis Pharmaceuticals, Janssen Pharmaceuticals, and Singhealth Foundation.